2021
DOI: 10.1016/j.adro.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Telehealth in Radiation Oncology: Rapid Integration During COVID-19 and Its Future Role in Our Practice

Abstract: Introduction The widespread coronavirus disease 2019 (COVID-19) has resulted in significant changes in care delivery among radiation oncology practices and demanded the rapid incorporation of telehealth. However, the impact of a large-scale transition to telehealth in radiation oncology on patient access to care and the viability of care delivery are largely unknown. In this manuscript, we review our implementation and report data on patient access to care and billing implications. As telehealth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Providing practical guidelines for implementing and using telehealth effectively has motivated different researchers during the COVID-19 pandemic [ 35 , 66 , 80 ]. Different clinicians were motivated to share their best practices in using telehealth to provide guidelines to others who will assist them in continuing to provide care services during the pandemic, such as gynaecology care [ 33 ], otolaryngology care [ 37 ], ophthalmology care [ 81 ], prostate cancer care [ 20 ], radiation oncology care [ 41 ], children with respiratory illnesses care [ 89 ] and physician care [ 27 ]. Furthermore, providing guidelines to perform neurological exams remotely was the main motivation of [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing practical guidelines for implementing and using telehealth effectively has motivated different researchers during the COVID-19 pandemic [ 35 , 66 , 80 ]. Different clinicians were motivated to share their best practices in using telehealth to provide guidelines to others who will assist them in continuing to provide care services during the pandemic, such as gynaecology care [ 33 ], otolaryngology care [ 37 ], ophthalmology care [ 81 ], prostate cancer care [ 20 ], radiation oncology care [ 41 ], children with respiratory illnesses care [ 89 ] and physician care [ 27 ]. Furthermore, providing guidelines to perform neurological exams remotely was the main motivation of [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, numerous studies recommended the implementation and expansion of telehealth because of its essential role in the continuation of patient care during the current pandemic and beyond [ 13 , 14 , 39 , 41 ]. Telehealth expansion was recommended to improve access to care of underserved populations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the costs associated with the technology required for telemedicine visits it is possible that widespread adoption could increase healthcare disparities amongst low income populations [16] or the elderly [17]. This may be particularly true for telemedicine visits requiring a video platform [18] as a prior study found that certain demographic characteristics such as age, race and income were associated with telemedicine use and ability to interface by video [19]. Efforts to overcome these barriers include the distribution of tablets by the VA to high need veterans [20].…”
Section: Discussionmentioning
confidence: 99%
“…Goenka et al . implemented telemedicine consultation for radiation-oncology and effectively lessoned the in person visit from 100% to 21% [195] . The rapid developments in supportive technologies are the future of TM including POC diagnostics and laboratory measurements to care the patients effectively while staying at their home [196] .…”
Section: Preventive Strategies For Covid-19mentioning
confidence: 99%